Iodide‐Capped PbS Quantum Dots: Full Optical Characterization of a Versatile Absorber. (21st January 2015) - Stadler, Philipp; Mohamed, Shaimaa A.; Gasiorowski, Jacek; Sytnyk, Mykhailo; Yakunin, Sergii; Scharber, Markus C.; Enengl, Christina; Enengl, Sandra; Egbe, Daniel A. M.; El‐Mansy, Mabrouk K.; Obayya, Salah S. A.; Sariciftci, N. Serdar; et al.
<x xml:space="preserve">Abstract</x> Lead sulfide quantum dots represent an emerging photovoltaic absorber material. While their associated optical qualities are true for the colloidal solution phase, they change upon processing into thin‐films. A detailed view to the optical key‐parameters during solid‐film development is presented and the limits and outlooks for this versatile and promising absorber are discussed. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>